Corporate reporting and accouting for externalities / Jeffrey Unerman, Jan Bebbington, Brendan O Dwyer. - Unerman, Jeffrey.
Externalities comprise economic, social and/or environmental impacts arising from the activities of an entity that are borne by others, at least in the short term. As they do not feedback directly into immediate financial consequences for the entity, they tend to be outside the remit of financial reporting. A dispersed academic accounting literature on externalities has hitherto developed separately from concerns about what information is appropriate to report on corporate performance. This paper develops insights into accounting for, and reporting of, externalities that are intended to improve the use of externalities information in breaking down silos between the traditionally discrete domains of financial reporting and sustainability reporting, and between silos within sustainability reporting. Challenges in such use of externalities information are explored, including difficulties inherent in the quantification of externalities. The paper also highlights ways in which externalities can progressively become internalised, thereby bringing them more readily within the domain of economically focused financial reporting practices. An agenda for further research to help enhance the accounting for, and reporting of, externalities is also proposed.